Ketika Hukum Menyentuh Ibadah: Kajian tentang Aturan Pengeras Suara di Masjid Perspektif Sosiologi Hukum - Kustana (Al-Ulum, 2024)
This research examines the social dynamics and public reactions to mosque loudspeaker regulations in Indonesia, both on social media and in mosques in Bandung, West Java. The study is based on the Circular Letter of the Minister of Religious Affairs No. 1 of 2024, which outlines guidelines for the observance of Ramadan and Eid al-Fitr 1445 H/2024 M, including rules on the use of mosque loudspeakers. Data were collected using a qualitative method through online observation and interviews with religious leaders and interfaith community members in Bandung, West Java.  The findings reveal that many people on social media oppose the regulation, citing emotional concerns and fears that it may disrupt religious traditions. However, in reality, its implementation has garnered widespread support. Several mosques, such as Masjid Al-Hasanah, Masjid Kifayatul Akhyar, and Masjid Raya Bandung, back the policy to foster tolerance and maintain good interfaith relations. Even in predominantly Muslim areas, the regulation is seen as important for respecting the needs of residents who require peace, such as those resting, working, or ill. This research concludes that the implementation of the regulation should consider diverse social contexts and be sensitive to religious pluralism. Additionally, further dialogue is needed to preserve social harmony in a pluralistic society.